2021
DOI: 10.1155/2021/1334571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Immune-Related Biomarker Model Based on the CircRNA-Associated Regulatory Network for Esophageal Carcinoma

Abstract: Esophageal carcinoma (ESCA) is one of the most frequent types of malignant tumor that has a dismal prognosis. This research applied datasets aimed from the GEO and TCGA to create a prognostic signature for forecasting the clinical outcome of ESCA patients on the basis of a circRNA-associated regulatory network. Methods. A regulatory network associated with ESCA was established based on transcriptome data of circRNAs, miRNAs, and mRNAs. Functional annotations were implemented to further explore the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…Our study confirmed that the expression levels of the three NRGs were significantly associated with immune cell infiltration in ESCA. Early findings suggested that abundant CD8+ T cells and CD4+ T cells could be prognostic indicators for the clinical outcome in cancers [40,41]. Our results are consistent with the previous reports suggesting that TNFRSF10B expression associated with high CD8+ T cell abundance may indicate better clinical outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Our study confirmed that the expression levels of the three NRGs were significantly associated with immune cell infiltration in ESCA. Early findings suggested that abundant CD8+ T cells and CD4+ T cells could be prognostic indicators for the clinical outcome in cancers [40,41]. Our results are consistent with the previous reports suggesting that TNFRSF10B expression associated with high CD8+ T cell abundance may indicate better clinical outcomes.…”
Section: Discussionsupporting
confidence: 93%